The Problems of Bullying toward Students' Learning Achievements at Grade V SD Negeri 23 Lolong - Ummy Khaira, Nurul; Susilawati, Susilawati; Yanda, Yilma (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2023)
This study aims to identify the impact of bullying on children's achievement in class V SDN 23 Lolong. This research uses a qualitative approach. The case subjects in this study consisted of fifth grade teachers and students. Data collection techniques used are observation, interviews and documentation. The results showed that bullying behavior was very influential on the character, interests, and learning values ​​of students. Generally, this bullying behavior is carried out verbally in the form of insults or innuendos to weak students. In this case, the teacher plays an important role in preventing bullying. (1) The teacher gives an understanding to the students that the bullying behavior is a disgraceful act. (2) The teacher explains the bad impact of the bullying to the students. (3) The teacher advises, guides, and supports students to become better. It is also hoped that there will be cooperation between teachers and parents in the children's learning process and pay attention to the bad attitudes of children in their environment